Caste in the 21st century: from system to elements - Shah, A.M. (2007)
The argument that while caste as a system is more or less dead, individual castes are flourishing is widely accepted. However, the notion of "caste as a system" is derived mainly from studies of the rural rather than the urban community. In this article, individual caste is seen in the context of both rural and urban communities and its several aspects, particularly the rule of endogamy as its defining criterion, are analysed at some length and some implications of the analysis are pointed out. - Reproduced.
Keywords: Caste - 21st century; Caste